Impact of Innovation in Sensory Marketing on Local Brand Image, Satisfaction and Return Intention of Tourist to Ha Giang Destination - Lam, Tran Thi; Ngoan, Do Thi; Anh, Le Thi Tu (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 4, 2022)
With the prospect that the COVID-19 epidemic will be basically controlled, many provinces and cities in Vietnam in general and Ha Giang province in particular are actively developing and implementing plans to accelerate the speed of tourism recovery, ensure safety, adapt to the new normal and aim to achieve the goal of developing the tourism industry into a spearhead economic sector. To achieve those aims, the pillar of development needs to be directed toward innovation, particularly innovation in marketing activities. This study focuses on analyzing the influence of sensory marketing on local brand image, satisfaction, and tourist retention at tourist destinations in Ha Giang province. Through data obtained from 204 tourists who have experienced Ha Giang tourism, the results show that sensory marketing through taste, sight, and touch has a direct influence on the return intention of tourists, or an influence to return indirectly through local brand image and tourist satisfaction. Therefore, the authors have proposed some solutions for stakeholders to innovate Ha Giang tourism through sensory marketing.